The Effect of Hysteroscopy on Fertility in Women with Unexplained Infertility - Rıza Dur; Betül Ahat; Ayşe Yalçınkaya Yılmaz; Cem Yağmur Özdemir; Mine Kanat Pektaş (Gazi Medical Journal)
Objective: This study aimed to investigate how undergoing hysteroscopy affects the reproductive rates of women with unexplained infertility. Methods: A total of 145 women who were aged between 20 and 40 years, who had been diagnosed with unexplained infertility and who underwent hysteroscopy at the study center between 1 January 2021 and 1 January 2022 were enrolled in this study. All patients who underwent hysteroscopy were put to an 18-month-long follow-up period. Results: The clinical pregnancy rate was 43.4%, whereas the live birth rate was 38.6% in this cohort. Average time to pregnancy took 5.6±1.8 months (range: 2-9 months). The mode of conception was unassisted in 28 pregnancies (44.4%) whereas the mode of conception was ovarian stimulation combined with intrauterine insemination in 23 pregnancies (36.5%) and in vitro fertilization in 12 pregnancies (19.1%). The patients who were able to conceive after hysteroscopy had significantly younger age, lower gravidity, and parity than those who failed to conceive (p=0.008, p=0.005 and p=0.001, respectively). The patients who successfully gave birth to living newborns after hysteroscopy had significantly younger age, lower gravidity, and parity than those who failed to deliver (p=0.040, p=0.003 and p=0.001, respectively). Septum resection was significantly more frequent and adhesiolysis was significantly less frequent in patients who were able to give birth to living newborns after hysteroscopy (p=0.038 and p=0.014, respectively). Conclusion: Hysteroscopy appears to have a positive impact on live birth rates in women with unexplained infertility.